Active Learning for the Kingdom of God - Lambert, Lake (Teaching theology and religion, 2000)
At the same time that teachers in theology and religion have been encouraged to consider how their personal identities affect their teaching, there has also been increased interest in active learning strategies. This essay argues that these two initiatives may be in conflict if the communal commitments of the instructor do not mirror the democratic commitments inherent to most active learning pedagogies. As a teacher of theology and ethics who is ultimately not committed to democracy but to the Kingdom of God, I have sought to develop learning strategies which avoid student passivity while focusing on the church as a foretaste to God's Kingdom. My consideration of this dilemma has drawn me to the educational philosophies of both John Dewey and Stanley Hauerwas, and in response to them I outline an active learning strategy which envisions the Christian church as a living tradition with students as dialogue partners and contributors to it.